Novye i utočnennye ėtimologii akkadskich anatomičeskich terminov (po materialam «Semitskogo ėtimologičeskogo slovarja» - Kogan, Leonid E. (Gs Diakonoff)
engl. Resümee: New Etymologies for the Akkadian Anatomic Lexicon (Based on the First Volume of Semitic Etymological Dictionary)